2020
DOI: 10.1039/d0ta01553a
|View full text |Cite
|
Sign up to set email alerts
|

Anti-freezing flexible aqueous Zn–MnO2 batteries working at −35 °C enabled by a borax-crosslinked polyvinyl alcohol/glycerol gel electrolyte

Abstract: An anti-freezing gel electrolyte with an ultralow freezing point below −60 °C is developed for assembling high-performance flexible aqueous Zn–MnO2 batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 239 publications
(138 citation statements)
references
References 75 publications
1
132
0
Order By: Relevance
“…Chen et al introduced a Zn-MnO 2 battery and used borax-crosslinked PVA/glycerol hydrogel electrolytes that worked at −35 • C. The presence of glycerol could strongly interact with the PVA chains and inhibited the formation of ice crystals within the hydrogel network. The battery achieved an energy density of 46.8 mWh cm −3 at 25 • C and of 25.8 mWh cm −3 at −35 • C [212]. Other multivalent ions batteries that could work at different temperatures using different hydrogel electrolytes have been reported to improve the potential window [213][214][215].…”
Section: Polymer Hydrogel Electrolytes For Energy Conversion Devicesmentioning
confidence: 99%
“…Chen et al introduced a Zn-MnO 2 battery and used borax-crosslinked PVA/glycerol hydrogel electrolytes that worked at −35 • C. The presence of glycerol could strongly interact with the PVA chains and inhibited the formation of ice crystals within the hydrogel network. The battery achieved an energy density of 46.8 mWh cm −3 at 25 • C and of 25.8 mWh cm −3 at −35 • C [212]. Other multivalent ions batteries that could work at different temperatures using different hydrogel electrolytes have been reported to improve the potential window [213][214][215].…”
Section: Polymer Hydrogel Electrolytes For Energy Conversion Devicesmentioning
confidence: 99%
“…As one of the most promising cathode materials, MnO 2 possesses the merits of low cost, high theoretical capacity (308 mAh g −1 , based on one electron reaction), high output voltage (∼1.4 V), and environmental friendliness (Jin et al, 2019;Chen et al, 2020). Ever since Yamamoto et al developed Zn//ZnSO 4 //MnO 2 cell chemistry in 1986 for the first time, lots of impressive works have been dedicated to this field (Yamamoto and Shoji, 1986;Guo et al, 2020;Xie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Nyquist plots in Figure 1E , the ionic conductivity values of gel electrolytes can be calculated. The calculation details can be found in our previous reports (Chen et al, 2020 ; Zhou et al, 2020 ). At a temperature of 20°C, the PAM/GO/EG gel electrolyte demonstrates a high ionic conductivity of 19.8 mS cm −1 , which drops to 17.9 and 14.9 mS cm −1 when the temperature declines to 0 and −20°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that adding cryoprotectants such as glycerol and ethylene glycol (EG) into gel electrolytes can realize good anti-freezing capabilities (Mo et al, 2019 ; Zhou et al, 2020 ). In our previous report, we developed a borax-cross-linked PVA/glycerol gel electrolyte, in which glycerol can interact with PVA chains strongly, thus effectively preventing the formation of ice crystals within the whole gel network (Chen et al, 2020 ). Even at −20°C, it still shows a high ionic conductivity of 15.9 mS cm −1 and great mechanical properties.…”
Section: Introductionmentioning
confidence: 99%